Epigenetic mechanism controls PDK4 gene activation before and after exercise therapy following artificial knee arthroplasty - Kamo T (Dove Medical Press, 2019)
Tomohiro Kamo,1 Satoshi Kurose,1 Hiroshi Ohno,2 Minoru Murata,2 Masaki Hashiyada,3 Takanori Saito,2 Yutaka Kimura11Department of Health Science, Kansai Medical University, Osaka, Japan; 2Department of Orthopaedic Surgery, Kansai Medical University Hospital, Osaka, Japan; 3Department of Forensic Medicine, Kansai Medical University, Osaka, JapanPurpose: DNA methylation is thought to play a role in exercise-induced gene expression. We aimed to examine changes in muscular strength and body composition in elderly patients with end-stage knee osteoarthritis before and after artificial knee arthroplasty and exercise therapy. We aimed to confirm the relationship between DNA methylation and body composition, using the methylation rate of the pyruvate dehydrogenase kinase 4 (PDK4) gene that regulates skeletal muscle and fat metabolism.Patients and methods: Patients underwent artificial knee arthroplasty between April 2017 and June 2017 at Kansai Medical University Hospital. Six patients (seven knees) were included in the analysis (four males/two females; average age, 75.7 years; body mass index, 25.1 kg/m2). Body composition and knee extension muscle strength were measured before surgery and 5 months after surgery. Rehabilitation was performed for 3 months after surgery. In the remaining 2 months, patients performed resistance training and aerobic exercise using an ergometer for 20 mins, twice a week. A biopsy of the vastus medialis was taken during surgery and 5 months post-surgery. Biopsy samples were treated with bisulfite after DNA extraction, and DNA methylation rate was calculated.Results: Body weight (P=0.046), total weight (P=0.027), and total fat mass (P=0.028) were significantly lower 5 months postoperatively than preoperatively. Five months post-surgery, the PDK4 gene was significantly more hypomethylated at eight sites in the CpG island, compared to pre-surgery. There was a significant correlation (r=0.88, P=0.02) between promoter region hypomethylation and weight loss. Total methylation rate and weight loss were significantly correlated (r=0.829, P=0.042). Total methylation rate and decrease in total fat mass showed a positive trending relationship (r=0.812, P=0.05).Conclusion: Rehabilitative exercise resulted in significant decreases in weight and body fat. Hypomethylation of the PDK4 gene promoter region signified the effect of postoperative management focus on exercise therapy on weight and fat loss.Keywords: rehabilitation, elderly person, muscle biopsy, methylation